Construction of Creative Problem-Solving Abilities Test for 7th Grade Students in a Special Science-Mathematics Class - Khansumrit, Supansa; Seetee, Navara (Ratchaphruek Journal, 2023)
The objectives of this research were to construct and find a quality of creative problem-solving abilities test for grade 7 students in a special science-mathematics classroom, and find a quality of parallel form of the test. The samples were 33 grade 7 students in the special science-mathematics classroom of a schools in Samut Prakan province, which was obtained by purposive sampling. The creative problem-solving abilities test is a situational and subjective test with general and specific rubrics. Difficulty index, discrimination index, Cronbach’s alpha coefficient, and Pearson’s correlation coefficient were conducted. The results showed that the creative problem-solving abilities test consisted of 3 scenarios, the difficulty index ranged from 0.358-0.478, the discrimination index ranged from 0.519-0.741, and reliability of the whole test was 0.90. The reliability of the parallel test ranged from 0.90-0.95. Pearson’s correlation coefficient between the two forms was 0.918. It indicated that the created test have a quality could be used as parallel test for before and after or the whole test as appropriate.